2022
DOI: 10.1101/2022.03.21.485220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recruitment of clathrin to intracellular membranes is sufficient for vesicle formation

Abstract: The formation of a clathrin-coated vesicle is a major membrane remodeling process that is crucial for membrane traffic in cells. Besides clathrin, these vesicles contain at least 100 different proteins although it is unclear how many are essential for the formation of the vesicle. Here, we show that intracellular clathrin-coated formation can be induced in living cells using minimal machinery and that it can be achieved on various membranes, including the mitochondrial outer membrane. Chemical heterodimerizati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Intriguingly, some large and bright clathrin structures colocalized with mitochondria (yellow arrowheads in Figure 6d), suggesting a newly discovered role of mitochondria in forming clathrin-coated vesicles. 29 Together, Re-MMI unraveled complex spatial organizations and potential interactions between intracellular structures in fixed cells, which are increasingly recognized as pivotal for diverse cellular functions. Experimental Validation of Re-MMI in Live-Cell Imaging.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Intriguingly, some large and bright clathrin structures colocalized with mitochondria (yellow arrowheads in Figure 6d), suggesting a newly discovered role of mitochondria in forming clathrin-coated vesicles. 29 Together, Re-MMI unraveled complex spatial organizations and potential interactions between intracellular structures in fixed cells, which are increasingly recognized as pivotal for diverse cellular functions. Experimental Validation of Re-MMI in Live-Cell Imaging.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Recent proteomic analyses have provided the first detailed mechanistic insights into machinery required for generation of TOM20 + MDVs, revealing that tubulation of mitochondrial membranes during MDV biogenesis is driven by the mitochondrial Rho GTPases MIRO1 and MIRO2 along microtubules prior to DRP1 recruitment and scission [41]. Reconstituting clathrin delivery to mitochondria also promotes mitochondrial protrusions (which the authors termed MitoPits), suggesting an alternative mechanism of MDV production [42]. Early studies revealed that MDVs Glossary AAA proteases: ubiquitous family of ATP-dependent proteases embedded in the IMM, characterised by the structural conservation of a central ATPase domain called the AAA module.…”
Section: Mitochondrial-derived Vesiclesmentioning
confidence: 99%
“…Interestingly, a second study, which has recently appeared on bioRxiv ( 9 ), takes an entirely different experimental approach to produce data that ultimately supports a similar set of conclusions. The investigative team led by Küey and Royle recruited clathrin artificially to the surfaces of mitochondria, which have high curvatures, similar to the ridges used in the study by Cail et al ( 8 ).…”
mentioning
confidence: 92%
“…Collectively, the studies by Cail et al ( 8 ) and Küey et al ( 9 ) suggest that both clathrin and its adaptor network play important roles in generating membrane curvature. When clathrin-coated vesicles bud from the relatively flat plasma membrane, both the adaptors and clathrin are required to complete the process.…”
mentioning
confidence: 99%
See 1 more Smart Citation